Prevalence and associated factors of depression in caregivers of patients with stroke at King Chulalongkorn Memorial Hospital. - Pakpakorn, R.; Kanchanatawan, B.; Charnnarong , N. (Chulalongkorn Medical Journal, 2023)
Background : Stroke is a leading cause of death and disability. Many caregivers are at risk of developing depressive symptoms. However, there are few studies focusing on this topic in Thailand. Objective : To estimate the prevalence and associated factors of depression in caregivers of patients with stroke at King Chulalongkorn Memorial Hospital. Design : A cross – sectional descriptive study. Setting : Department of Medicine and Department of Rehabilitation Medicine, at King Chulalongkorn Memorial Hospital. Materials and Methods : A total of 96 stroke caregivers participated in this study. Data were collected by using self-report questionnaire, Barthel Index Thai version, Zarit Burden Interview (Thai version), social support questionnaire and Beck Depression Inventory (Thai version). The statistics, including percentage, mean, standard deviation, chi-square and multiple logistic regression analysis were applied for evaluation. Results : The prevalence of depression in caregivers was 44.8 percent. Caregivers’ factors significantly related to depression were: inadequate income, less than 5 hours of sleep, the difficulty in care giving to patient, low social support, high caregivers’ burden. Patients’ factor significantly related to depression in caregivers was low daily activities. The predictive factors for depression in caregivers were inadequate income (OR = 4.20 95% CI = 1.31 - 13.39), less than 5 hours of sleep (OR = 5.03 95% CI = 1.51 - 16.80) and high caregivers’ burden (OR = 9.05 95% CI = 2.68 - 30.55). These factors increase the risk of depression in stroke patients’ caregivers. Conclusion : Physicians should be interested on screening for depression in patients’ caregivers, in order to provide proper management and improve quality of care for stroke patients.